Desulfurisasi Batubara dengan Metode Leaching Menggunakan Pelarut Asam Klorida (HCl) - Syafril Maidi; Yunasril Yunasril (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Combustion of coal has high sulphur content causes environmental pollution, damage(corrosive) and shortens the life of industrial plant equipment. Combustion of has high sulphurcontent produces Sulfur dioxide (SO2) which can disrupt humanlife, such as causing tightness inthe respiratory tract, causing acid rain and corrosion on plant equipment. So that coal can beused as fuel then desulfurization process is carried out first. Desulfurization of coal is needed notonly to minimize environmental pollution caused by emissions of Sulphur dioxide duringcombustion, but also to improve the quality of coal. Desulfurization of coal is a process ofreducing sulphur content from coal. The desulfurization process in this research uses a chemicalmethod with Hydrochloric acid (HCl) solvent. Coal that will be desulfurized is coal from flemmingseam produced by PT. Nusa Alam Lestari Site Sinamar, Dharmasraya Regency, West SumateraProvince. Flemming seam has a thickness of up to 1,2 meters. This layer has calorific valuesbetween 5100 – 5500 kcal/kg. This coal is lignite with an average sulphur content of 1,5 – 2,2%.This coal is treated by modifying the concentration of Hydrochoric acid (HCl), which is 0,4 M, 0,6M, 0,8 M, 1 M, and 1,2 M. After leaching the coal, the next process is to test sulphur content withsulfur analyzer. Of all variations in the concentration of Hydrochloric acid (HCl), the optimumconcentration is obtained, HCl 0,8 M which can reduce sulphur levels to 0,59%.Keywords: desulfurization, coal, sulphur, Hydrochloric acid, combustion.